2006
DOI: 10.1029/2004ja010683
|View full text |Cite
|
Sign up to set email alerts
|

Large variations in the thermosphere and ionosphere during minor geomagnetic disturbances in April 2002 and their association with IMF By

Abstract: 1] We investigate the variations in the thermosphere and ionosphere using multiinstrument observations during the April 2002 period, with a particular focus on periods during small geomagnetic disturbances. Large and long-lasting reductions in the daytime electron density were observed at midlatitudes by incoherent scatter radars, ionosondes, and GPS receivers. These reductions reached 30-50% and were observed over an extended longitudinal area. They propagated to middle latitudes (35-40°N) in the case of a we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 42 publications
5
31
0
1
Order By: Relevance
“…3). The results of our calculations (Table 1) are confirmed by GUVI/TIMED observations, which also show a low [O]/[N 2 ] column ratio for the day of negative Q-disturbance on 16 April 2002 (Goncharenko et al, 2006). The ground state of the thermosphere with the northward meridional wind did take place on 16 April.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…3). The results of our calculations (Table 1) are confirmed by GUVI/TIMED observations, which also show a low [O]/[N 2 ] column ratio for the day of negative Q-disturbance on 16 April 2002 (Goncharenko et al, 2006). The ground state of the thermosphere with the northward meridional wind did take place on 16 April.…”
Section: Discussionsupporting
confidence: 77%
“…The ground state of the thermosphere with the northward meridional wind did take place on 16 April. According to Millstone Hill estimations, V nx was northward until 21:00 UT (Goncharenko et al, 2006, their Fig. 17).…”
Section: Discussionmentioning
confidence: 99%
“…The calculated Tex are close to the Millstone Hill estimates for both periods, being larger than the NRLMSISE-00 (Picone et al, 2002) model predictions by about 100 K. A similar underestimation of the NRLMSISE-00 model Tex was noted by Lei et al (2004). The O/N 2 column ratio observed with the GUVI instrument for the 15/16 April 2002 period shows a 30-50% reduction from 15 April to 16 April in the Atlantic longitudinal sector (Goncharenko et al, 2006). A direct comparison of our [O] and [N 2 ] with the GUVI column observations is problematic due to many technical reasons (Goncharenko et al, 2006), however, our O/N 2 ratio at 300 km reduced to 07:30 LT (the local time of the GUVI observations) also exhibits a 40% reduction on 16 April with respect to 15 April.…”
Section: Discussionsupporting
confidence: 57%
“…On the other hand, neither one can exclude the high-latitude impact on the global circulation and thermospheric composition. Goncharenko et al (2006), for instance, revealed a pronounced negative Q-disturbance effect using the Millstone Hill ISR and TIMED observations and attributed it to IMF B y variations.…”
Section: Introductionmentioning
confidence: 99%
“…[29] Optical observations by Grossmann et al [2000] revealed a systematic (by 40% on average below MSIS-86) difference in atomic oxygen densities in the 130-175 km height range. The O/N 2 column ratio observed with the TIMED/GUVI instrument for the magnetically quiet period 15-16 April 2002 gave a 30-50% reduction of this ratio from 15 to 16 April in the Atlantic longitudinal sector [Goncharenko et al, 2006]. Neither MSIS-86 nor NRLMSISE-00 models describe such strong O/N 2 day-to-day variations.…”
Section: Seasonal Variationsmentioning
confidence: 96%